Decellularized extracellular matrix-based 3D nanofibrous scaffolds functionalized with polydopamine-reduced graphene oxide for neural tissue engineering - Silva, Daniela M. da (2023)
One of the exciting prospects of using decellularized extracellular matrices (ECM) lies in their biochemical profile of preserved components, many of which are regeneration-permissive. Herein, a decellularized ECM from adipose tissue (adECM) was explored to design a scaffolding strategy for the challenging repair of the neural tissue. Targeting the recreation of the nano-scaled architecture of native ECM, adECM was first processed into nanofibers by electrospinning to produce bidimensional platforms. These were further shaped into three-dimensional (3D) nanofibrous constructs by gas foaming. The conversion into a 3D microenvironment of nanofibrous walls was assisted by blending the adECM with lactide-caprolactone copolymers, wherein tuning the adECM/copolymer ratio along with the amount of caprolactone in the copolymer led to modulating the mechanical properties towards soft, yet structurally stable, 3D constructs. In view of boosting their performance to guide neural stem cell fate, adECM-based platforms were doped with a bioinspired surface modification relying on polydopamine functionalized reduced graphene oxide (PDA-rGO). These adECM-based 3D constructs revealed a permissive microenvironment for neural stem cells (NSCs) to adhere, grow, and migrate throughout the microporosity, owing to the synergy between the unique biochemical features of the adECM and the nanofibrous architecture. NSC responded differently depending on the adECM-based architecture–nanofibrous bidimensional, or 3D design. The 3D spatial arrangement of the nanofibers – induced by the gas foaming – exhibited a remarkable effect on NSCs’ phenotype determination and neurite formation, thereby reinforcing the critical importance of engineering scaffolds with multiple length-scale architecture. Furthermore, PDA-rGO promoted the differentiation of NSC towards the neuronal lineage. Specifically in 3D, it significantly increases the levels of Tuj1 and MAP2 a/b isoforms, confirming its effectiveness in boosting neuronal differentiation and neuritogenesis.